Предмет: Алгебра,
автор: панда78
помогите упростить выражение, с полным решением ((пожалуйста((
Приложения:
Ответы
Автор ответа:
0
Решение
Применим формулы:
1 - sinα = 2sin∧2x(45² - α)
cosα - sinα = √2*(sin∧2x(45² - α))
Итак получаем:
2sin∧2x(45² - α) / ( - √2*(sin∧2x(45² - α)) = - 2/√2 = √2
Применим формулы:
1 - sinα = 2sin∧2x(45² - α)
cosα - sinα = √2*(sin∧2x(45² - α))
Итак получаем:
2sin∧2x(45² - α) / ( - √2*(sin∧2x(45² - α)) = - 2/√2 = √2
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Английский язык,
автор: oakmerden
Предмет: Английский язык,
автор: Аноним
Предмет: Алгебра,
автор: sardoeva
Предмет: Математика,
автор: vvvmmmsss